Standardization of Mastery Kitab Kuning in Nurul Hakim Islamic Boarding School West Nusa Tenggara - Mulyani Mudis Taruna (Analisa: Journal of Social Science and Religion, 2012)
The focus of this research is the standardization of mastery “kitab kuning” in the Salaf Boarding School “Nurul Hakim” West Nusa Tenggara. The specific study was conducted at Darul Hikmah Li Ma’had Aly Al Fiqh wa Al-Da’wah. The findings of the research showed that the jargon “al-mukhafadlat ‘ala al-qadim ash-shalih wa al-akhdzu bi al-jadid al-ash- lah” or sticking to the old traditions and opening it up to contemporary phenomena inspired boarding school to follow the development of increasingly complex and global challenges. Ma’had ‘Aly Darul Hikmah Li Al Fiqh wa Al-Da’wah still refers to “kitab kuning” as the standard control by mahasantri. Benchmarking was based on the evaluation conducted each year by MPK-OS and set by the Majlis Kiai. Orientation for the determination was in accordance with the “kitab kuning” or study program taught in the Ma’had. The evaluation model which was developed in Ma’had ‘Aly was not different from the evaluation model which was developed at public universities, namely the evaluation of mid-semester and final semester. Another evaluation was an evaluation of each chapter in each study on the “Kitab Kuning” with sorogan model it was implemented in salaf pesantren students. Nev- ertheless, the standardization of control of the “Kitab Kuning” was in the hand of boarding school authorities as a part of developed formal education program.